Integration of urban farming and waste management in realizing a sustainable environment in Dauh Puri Kaja Village - Sarahswati, Made Dwi Kanaka; Wedagama, Dew Ayu Trisna Adhiswari (Penamas: Journal of Community Service, 2025)
Due to the increasing amount of waste and the limited amount of green land in cities, environmental issues are becoming a significant challenge to realizing a sustainable environment. To raise public awareness about the importance of environmental management, this community service program combines the idea of urban farming with the concept of 3R-based waste management (reduce, reuse, recycle). The activity was held in Dauh Puri Kaja Village, Denpasar, and involved hands-on practice and training in waste sorting, processing organic waste into compost, and utilizing it for urban farming. The program began with training for residents at the Balai Banjar. Then, the processed compost fertilizer was distributed at the Waste Management Site (TPS), and instructions were given on how to use it for urban farming.  The results show that the community better understands how to utilize compost for household-scale farming and properly segregate waste. In the long run, it is expected that this program will significantly impact the community by teaching them how to manage waste and make the best use of green spaces. This will encourage a cleaner and more sustainable environment.